A novel method for transcatheter closure of atrial septal defect within an aneurysm of the fossa ovalis: double sheath technique. Issue 6 (1st December 2000) - Peuster, M; Kaulitz, R; Hausdorf, G
Abstract : An aneurysm of the fossa ovalis is frequently associated with an atrial septal defect. Intervention with transcatheter closure of such defects may be difficult since it bears the risk of inadvertent deployment of the device with both umbrellas in the right or left atrium. A novel technique for the closure of such multiperforated aneurysms of the fossa ovalis, which allows central positioning and controlled deployment of the device, is reported.